Possible antioxidant mechanism of coenzyme Q10 in diabetes: impact on Sirt1/Nrf2 signaling pathways - Fatemeh Samimi; Maryam Baazm; Ebrahim Eftekhar; Sadegh Rajabi; Mohammad Taghi Goodarzi; Farideh Jalali Mashayekhi (Wolters Kluwer Medknow Publications, 2019)
Oxidative stress is a major complication in diabetes mellitus. The aim of this study was to investigate potential antioxidant activity of coenzyme Q10 (Co Q10) against hyperglycemia-induced oxidative stress in diabetic rat and unraveling its mechanism of action by focusing on silent information regulator 1 (Sirt1) and nuclear factor E2-related factor 2 (Nrf2) mRNA expression level. Furthermore, the activity of two Nrf2-dependent antioxidant enzymes (superoxide dismutase and catalase) in the liver of diabetic rats was studied. After induction of diabetes in rats using streptozotocin (55 mg/kg), rats were divided into five groups of six each. Groups 1 and 2 (healthy control groups) were injected with isotonic saline or sesame oil; group 3 received Co Q10 (10 mg /Kg /day), group 4, as a diabetic control, received sesame oil; and group 5 was diabetic rats treated with Co Q10. Afterwards, serum and liver samples were collected, and oxidative stress markers, lipid profile, as well as the expression of Sirt1 and Nrf2 genes were measured. Diabetes induction significantly reduced expression level of Sirt1 and Nrf2 mRNAs and also declined catalase, superoxide dismutase activities, and total thiol groups levels in diabetic group in comparison to healthy controls, while a significant increase was found in the levels of malondialdehyde and lipid profile. Co Q10 treatment significantly up-regulated Sirt1 and Nrf2 mRNA levels along with an increase in catalase activity in diabetic group as compared with untreated diabetic rats. Furthermore, Co Q10 caused a marked decrease in malondialdehyde levels and significantly improved lipid profile. Our data demonstrated that Co Q10 may exert its antioxidant activity in diabetes through the induction of Sirt1/Nrf2 gene expression.